Effectiveness Of Village Revenue and Spending Budget Management (APBDes) In 2020 In Kadu Village, Curug District, Tangerang Regency - Rina Kurniawati; Rahmawati; Yeni Widyastuti (International Journal of Social Sciences Review, 2021)
The focus of this research is to see how much effectiveness is in managing the 2020 Village Revenue and Expenditure Budget (APBDes) in Kadu Village, Curug District, Tangerang Regency. The problems in the research are: the weak management of APBDes in Kadu Village at the planning stage, still weak implementation of APBDes management in Kadu Village, budget management in the field of community empowerment and community development has not gone well, the financial budget for the implementation of village development has not been realized properly. The purpose of the research is to find out how much the Effectiveness of Village Revenue and Expenditure Budget Management (APBDes) in 2020 is in Kadu Village, Curug District, Tangerang Regency. The theory used is Gibson's theory of effectiveness, which includes indicators of careful planning, indicators of clarity of goals to be achieved, indicators of clarity of strategy for achieving goals, indicators of appropriate programming, indicators of facility and infrastructure availability , indicators of monitoring systems and educational controls, and indicators of a solid policy analysis and formulation process, (Tangkilisan 2005:141). Researchers used descriptive quantitative methods, with a total sample of 110 respondents, data collection techniques using saturated samples. The results obtained in this research reached 73% and were included in the effective category. Suggestions that can be recommended for research are to provide understanding and socialization of village financial budgets to village communities through village forums, improving community development and empowerment based on potential by conducting counseling and training on agricultural land management and forming farmer groups associations, and improving the quality of village apparatus resources by providing technical guidance to village officials and technical implementers of village financial management.